An investigation of antecedents and outcomes of accounting information quality: Evidence from SMEs - Nuraliati, Ayke; Astuti, Ayi; Ali Januarty, Tamy; Johan, Ahmad; Sudarmadi, Dedi (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
In an increasingly competitive business environment, high-quality accounting information is crucial for companies seeking improved performance—particularly small and medium-sized enterprises (SMEs) in the manufacturing sector. Accounting information quality not only influences internal decision-making but also fosters trust among stakeholders, including investors, creditors, and business partners. This study aims to examine the roles of innovation capability, risk propensity, moral standards, knowledge management, and the management accounting information system (MAIS) in shaping accounting information quality and financial performance. Data were collected through 318 questionnaires distributed to general managers, financial managers, chief accountants, and internal auditors in randomly selected manufacturing companies in Bandung City. The data were analyzed using the SEM-PLS approach to test the relationships among the studied variables. The results indicate that innovation capability, risk propensity, moral standards, and knowledge management significantly influence both the management accounting system and the quality of accounting information. In turn, the management accounting system and accounting information quality significantly affect financial performance. Based on these findings, this study recommends that company management adopt modern MAIS, as it is a critical component for achieving competitive advantage and long-term survival in today’s market.